Loss of CDYL Results in Suppression of CTNNB1 and Decreased Endometrial Receptivity - Zhou, Xiaowei; Xu, Bufang; Zhang, Dan; Jiang, Xiaoping; Chang, Hsun-Ming; Leung, Peter C. K.; Xia, Xiaoyu; Zhang, Aijun (Frontiers in Cell and Developmental Biology, 2020)
Impaired endometrial receptivity is one of the major causes of recurrent implantation failure (RIF), although the underlying molecular mechanism has not been fully elucidated. In present study, we demonstrated that Chromodomain Y like (CDYL) was highly expressed in the endometrium at mid-secretory phase during the normal menstrual cycles. However, the expression of CDYL was down-regulated in the endometrial tissues obtained from women with RIF, consistently with the protein level of LIF, which is a marker of endometrial receptivity. In CDYL-knockdown human endometrial Ishikawa cells, we identified 1738 differentially expressed genes. Importantly, the catenin beta 1 (CTNNB1) expression was dramatically reduced responding to the CDYL inhibition, both in Ishikawa cells as well as ¬the primary endometrial epithelial and stromal cells. In addition, the expression of CTNNB1was decreased in the endometrium from RIF patients as well. These results suggested that, the expression of CTNNB1 was regulated by CDYL in endometrium. The cell migration was impaired by CDYL-knockdown in Ishikawa cells and primary endometrial stromal cells, which could be rescued by CDYL or CTNNB1 overexpression. Collectively, our findings indicated that, the decreased expression of CDYL may suppress endometrial cell migration capability by affecting CTNNB1 expression, which would contribute to poor endometrial receptivity in women with RIF.